Pengembangan Media Audio Pop-Up Book Terhadap Unggah-Ungguh Bahasa Jawa Siswa SMP Negeri 2 Pare - Defany Fiqrotul Laely; Latif Nur Hasan (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Learning Javanese is included in learning ethics or politeness values, so it is very important to teach it in the world of education. As a tool to attract students' attention and want to learn Javanese, namely by developing learning media in the form of audio pop-up books. This research aims to explain: (1) the process of developing audio pop-up book, (2) the quality of audio pop-up book, (3) student responses to audio pop-up book learning media as a learning medium for uploading Javanese language material at SMP Negeri 2 Pare. This research uses research and development (R&D) methods with a four-D (4D) development model. The resulting data is in the form of oral and written. The data collection techniques used were observation, questionnaires and interviews. The instruments used were observation sheets, questionnaire sheets, and interview sheets. The results of this research are the product manufacturing process starting from needs analysis, product manufacturing plans, to the results of product development. to the final product. Validation from experts received a total percentage of 93.4% and total student responses received a percentage of 91.9% which was included in the